Analisis Pengawasan dalam Peningkatan Kinerja Pegawai SUPM Waiheru Ambon - Aprilya Layn; Mohamad Arsad Rahawarin; Maryam Salampessy (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study analyzes supervision as an effort to improve employee performance at the Intermediate Fisheries Business School (SUPM) Waiheru, Ambon. The research is grounded in the importance of supervision as a managerial function that ensures employee discipline, task clarity, accountability, and achievement of organizational objectives. A descriptive qualitative approach was applied through observation, interviews, and documentation involving school leaders and employees as key informants. The findings show that supervision at SUPM Waiheru has been implemented through direct and indirect mechanisms, including attendance monitoring, workplace observation, periodic inspection, monthly evaluation meetings, work reporting, and performance assessment through the employee performance target system. However, supervision has not yet been fully consistent and structured. Several employees still show weak discipline, limited initiative, and dependence on direct instructions from leaders. The study further reveals that effective supervision requires accurate information, timely feedback, objectivity, comprehensive coverage, and flexibility. Supervision improves performance when it is conducted not merely as control, but also as coaching, guidance, and motivation. The study implies that SUPM Waiheru needs clearer standard operating procedures, stronger monitoring technology, continuous employee development, and more participatory communication between leaders and employees.